Building a Copyright Legal Culture Through Awards to Book Authors: Building a Culture of Copyright Law Through the Giving of Appreciation to Authors - Happy Yulia Anggraeni; Yuyut Prayuti (IHSA Institute, 2022)
Universities in Indonesia have been known to act as educational and teaching institutions, as well as research and community service institutions. The function of Higher Education itself is to increase the added value of students, to produce trained and educated human resources in the fields of science, technology and art so that they can produce Intellectual Property through various research and innovation activities carried out. Universities are obliged to increase the participation of the academic community in supporting institutional performance and making a significant contribution to the community's economy as well as participating in IPR which is a form of real commitment in contributing and being an important part of the development of the National Innovation System (SINAS) in Indonesia. This type of research is normative legal research, with a statutory approach. Types and sources of primary research materials and sources of secondary research materials. The technique of collecting legal materials is through document studies (library studies), and data processing techniques using descriptive techniques. Finally, this study uses data analysis techniques with deductive logic, or processing legal materials by deductive means. This study concludes that efforts to increase awareness of respect for other people's copyrighted works are indeed not an easy job, must be supported by facilities and infrastructure that require very large costs. Support for academics, students, law enforcement officials, the government and the general public regarding copyright is very much needed, because the challenges that arise are not only in terms of the laws and regulations which always open up space to be interpreted differently, but also weak law enforcement, the lack of government contribution to fulfillment of educational data and lack of awareness of respecting copyright of ordinary people or those who are in the world of education, especially higher education..